Russian and Soviet View of the military-technical character of future war, 1877-2017 - Bellamy, Christopher D. (University of Edinburgh, 1991)
The Russian terms '(a) future war' and 'contemporary war(fare)' are sometimes used almost synonymously, sometimes with distinct nuances, the former now equating to 'World War III' in English. They have been used this way since the 1870s, when the volume of analysis of the effect of new technology on warfare increased. The character of future war forms a major part of Military Doctrine, and like Military Doctrine is divided into political and military-technical components. During most of the Soviet period, Doctrine was defined as the state's agreed system of views on the likely course and character of a future war, although it has recently been redefined as a system of views on the prevention of war. It is argued that this does not shift the character of future war from its central position in Doctrine. The Russians produced much analysis of 'future war' before 1914, including the only such work hitherto widely known outside Russia, Bliokh's Future War, which requires a reappraisal. Most of the Russian literature predicted the character of the Great War accurately. Military-scientific works constitute most of the analysis. There were a few fictional treatments of future war, although far fewer than in western languages. Although the demonstrable continuity between Imperial and Soviet writing on the subject transcends the 1917 Revolution, Marxist-Leninist emphasis on prediction reinforced the main stream of military analysis. The quality and quantity of Soviet analysis of the character of future war was particularly marked in the inter-war period, when it preoccupied some of the Soviet Union's most perceptive military thinkers and again foresaw the character of the next great war accurately. After World War II, analysis focused on the 'Revolution in Military Affairs' caused by the ballistic missile and nuclear warhead, the only area of 'future war' thinking hitherto extensively analysed in the west. Since 1945 scientific techniques for forecasting have been more fully developed and there is now an accepted definition of short-, mediumand long-term forecasts, the latter stretching 25 to 30 years ahead and now coinciding with the symbolic 2017 horizon. Throughout the period the General Staff and its associated military academies, which together form a network of future war 'think-tanks' have dominated the view of possible future war. This is now changing with the emergence of some well qualified analysts and respected organs outside the General Staff. The disparity between the highly futuristic views of the General Staff and the requirements of realpolitik appears to be growing. Throughout, concentration has focussed on a great war between major states and political systems. Internal and 'low-intensity' conflict have been neglected, the reasons for which are analysed.
The Russian and Soviet View of the military-technical character of future war, 1877-2017
Keywords: History; Military; Russia